2015
DOI: 10.1002/eat.22741
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, comparative pilot trial of family‐based interpersonal psychotherapy for reducing psychosocial symptoms, disordered‐eating, and excess weight gain in at‐risk preadolescents with loss‐of‐control‐eating

Abstract: Objective Preadolescent loss-of-control-eating (LOC-eating) is a risk factor for excess weight gain and binge-eating-disorder. We evaluated feasibility and acceptability of a preventive family-based interpersonal psychotherapy (FB-IPT) program. FB-IPT was compared to family-based health education (FB-HE) to evaluate changes in children’s psychosocial functioning, LOC-eating, and body mass. Method A randomized, controlled pilot trial was conducted with 29 children, 8 to 13 years who had overweight/obesity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 45 publications
0
63
0
Order By: Relevance
“…Items assessing abnormal eating behaviors and attitudes (food preoccupation, anorexia, or bulimia) were not changed significantly during treatment . Four studies reported follow‐up data only, reporting no change or a significant reduction in ED risk …”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Items assessing abnormal eating behaviors and attitudes (food preoccupation, anorexia, or bulimia) were not changed significantly during treatment . Four studies reported follow‐up data only, reporting no change or a significant reduction in ED risk …”
Section: Resultsmentioning
confidence: 98%
“…Meta‐analysis of the intervention arms from nine studies, with a combined sample of 491 participants, found no change in ED risk post‐intervention (Figure A; SMD [SE], −0.10 [0.10], P = 0.317, I 2 86%). A follow‐up measure of up to 4.6 years from baseline was reported in six studies, with a combined effect of −0.31 [0.13], P = 0.012, I 2 88% (Figure B) representing a reduction in ED risk. Funnel plots appeared symmetrical, and the classic fail‐safe N statistic estimated that 91 unpublished studies would be required for P > 0.05 at follow‐up, and therefore, publication bias is unlikely.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Strategies are also taught for parenting around topics related to disordered eating attitudes and behaviors, such as encouraging discussion of media images, praising their child for non-appearance related characteristics, and avoiding discussions of their own or other’s bodies in front of their child. Improving communication, increasing support, and reducing conflict within the family through interpersonal psychotherapy has been shown to be helpful for children with overweight/obesity and LOC eating by reducing LOC eating episodes and disordered eating attitudes [79]. As such, FBT elements focusing on communication within the parent-child relationship may be one mechanism through which to reduce disordered eating.…”
Section: Fbt Treatment Componentsmentioning
confidence: 99%